Muscle strength and ankle mobility for the gait parameters in diabetic neuropathies - Martinelli, Alessandra Rezende [UNESP]; Mantovani, Alessandra Madia [UNESP]; Nozabieli, Andrea Jeanne Lourenço [UNESP]; Ferreira, Dalva Minonroze Albuquerque [UNESP]; Barela, José Angelo [UNESP]; Camargo, Marcela Regina de [UNESP]; Fregonesi, Cristina Elena Prado Teles [UNESP] (Elsevier, 2013)
Aims: To evaluate the spatio-temporal variables of gait and the isometric muscle strength component of the ankle in patients with peripheral diabetic neuropathy. Also, verify the relationship between these variables and gait parameters. Methods: This study involved 25 diabetic peripheral neuropathy (DPN) participants (62.4 ± 8.36 years) and 27 age-matched healthy control individuals (64.48 ± 6.21 years). The assessment of the spatio-temporal parameters of gait was performed using an electronic baropodometry treadmill. Prior to the collection data, each participant was instructed to walk on the treadmill in her/his habitual self-selected speed. Results: Diabetic neuropathy group showed impairment of gait, with a smaller stride and length speed of the cycle, and increased duration of support time. Restricted dorsiflexion mobility and increased plantarflexion mobility were found, with a decrease in muscle strength of the dorsiflexors and plantiflexors. There was a significant relationship between plantiflexor muscle strength and the length and speed of the gait cycle. Also the muscle strengths of the plantiflexors and dorsiflexors, and the range of motion of dorsiflexion were predictors of gait performance. Conclusions: The ankle, muscle strength and ankle mobility variables could explain changes in gait speed and range of motion in patients with DPN, allowing for the application of preventive strategies. © 2012 Elsevier Ltd.
Keywords: Ankle; Diabetes mellitus; Gait; Joint mobility; Muscle strength; adult; ankle; ankle dorsiflexor muscle; ankle plantiflexor muscle; clinical article; controlled study; diabetic neuropathy; female; gait; gait disorder; human; joint limitation; joint mobility; male; muscle isometric contraction; muscle strength; muscle weakness; non insulin dependent diabetes mellitus; priority journal; range of motion; skeletal muscle; treadmill